Heat Transfer of nano fluids in an inclined channel under Magnetic field with heat source/sink - Srikanth, G V P N; G.Srinivas, Dr.; Gorthi, Raja Sekhar (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
We investigated theoretically the MHD flow of a nano-fluid past an inclined, oscillatory and permeable semi-infinite flat sinking sheet (S<0). The constant heat source and the thermal radiation are also considered. The slip velocity is oscillatory on time. The governing equations of the boundary layer are solved numerically using the R-K 6th order method. The influence of various parameters on velocity and heat transfer is analyzed. The increase in inclination of the sinking sheet, thinning the momentum boundary and enhancing the thermal boundary layers.